Defect induced, layer-modulated magnetism in ultrathin metallic PtSe2 - Avsar, Ahmet; Ciarrocchi, Alberto; Pizzochero, Michele; Unuchek, Dmitrii; Yazyev, Oleg V; Kis, Andras (Nature nanotechnology, 2019)
Defects are ubiquitous in solids and often introduce new properties that are absent in pristine materials. One of the opportunities offered by these crystal imperfections is an extrinsically induced long-range magnetic ordering1, a long-time subject of theoretical investigations1–3. Intrinsic, two-dimensional (2D) magnetic materials4–7 are attracting increasing attention for their unique properties, which include layer-dependent magnetism4 and electric field modulation6. Yet, to induce magnetism into otherwise non-magnetic 2D materials remains a challenge. Here we investigate magneto-transport properties of ultrathin PtSe2 crystals and demonstrate an unexpected magnetism. Our electrical measurements show the existence of either ferromagnetic or antiferromagnetic ground-state orderings that depends on the number of layers in this ultrathin material. The change in the device resistance on the application of a ~25 mT magnetic field is as high as 400 Ω with a magnetoresistance value of 5%. Our first-principles calculations suggest that surface magnetism induced by the presence of Pt vacancies and the Ruderman–Kittel–Kasuya–Yosida (RKKY) exchange couplings across ultrathin films of PtSe2 are responsible for the observed layer-dependent magnetism. Given the existence of such unavoidable growth-related vacancies in 2D materials8,9, these findings can expand the range of 2D ferromagnets into materials that would otherwise be overlooked.